Gearing to success with national breastfeeding programmes: The Becoming Breastfeeding Friendly (BBF) initiative experience - Rafael Pérez‐Escamilla; Fiona C. Dykes; Sally Kendall (Wiley, 2023)
Abstract Evidence‐based policy toolboxes are essential for decision makers to effectively invest in and scale up maternal‐child health and nutrition programs, and breastfeeding is no exception. This special issue focuses on the experiences implementing the Becoming Breastfeeding Friendly (BBF) toolbox in England, Scotland, and Wales. BBF is an initiative that includes a toolbox for decision making based on the Complex Adaptive System‐based Breastfeeding Gear Model. The BBF initiative experience in Great Britain presented in this special issue illustrates how versatile BBF is as it can be readily adapted to the specific application context. In this instance one country, England was trained by the Yale School of Public Health team that developed BBF. England, in turn, trained and assisted Scotland and Wales with the implementation and oversight of BBF in those countries. The positive experience implementing BBF in Great Britain is fully consistent with findings related to this initiative in other countries with contrasting economic, social, political and health care systems; including Germany, Ghana, Mexico, Myanmar, and Samoa. In all instances BBF has led to breastfeeding policy improvements with strong implications for enabling breastfeeding environments including maternity benefits, workforce development, the Baby Friendly Hospital Initiative and behavior change communication campaigns. In conclusion, BBF is a powerful tool to help guide the effective scaling up of evidence‐based programmes to advance breastfeeding protection, promotion and support globally.